INFLUENCE OF POLYSACCHARIDES ON PHYSICAL PROPERTIES OF PVA FILMS AND HYDROGELS BASED ON AQUEOUS EXTRACT OF THE MEDICINAL CHAMOMILE (MATRICARIA CHAMOMILLA) - ЛЯШОК, І. О.; ПЛАВАН, В. П.; КРЮКОВА, О. А.; ПОЛУШКІН, М. М.; ШВЕЦЬ, В. В.; ШАПОВАЛОВА, Я. С. (Technologies and Engineering, 2025)
Purpose. To determine the influence of polysaccharides on the physical properties of films and hydrogels composed of polyvinyl alcohol (PVA) based on the aqueous extract of the medicinal chamomile Matricaria chamomilla. Methodology. Compositions based on the aqueous extract of medicinal chamomile Matricaria chamomilla 10% PVA, 10% Kr and 5% KMK were prepared by mixing PVA/Kr and PVA/KMK solutions in a ratio of 1/1. Hydrogels were obtained by one-time freezing of compositions for 24 hours at a temperature of -15 oC, and films by the method of watering with subsequent drying under normal conditions. Sorption characteristics of hydrogels and films were determined by the gravimetric method in relation to distilled water and physiological NaCl solution. Rheological studies of PVA, PVA/Kr, PVA/KMK compositions were carried out using a rotary viscometer NDJ-9S (PRC) in accordance with DSTU 33–2003. Findings. It was established that the presence of medicinal starch and carboxymethyl starch in the composition of hydrogels based on the aqueous extract of chamomile leads to a decrease in the degree of swelling in distilled water and in physiological solution. It has been proven that the presence of starch and carboxymethyl starch polysaccharides in the composition of hydrogels based on the aqueous extract of chamomile leads to a decrease in the percentage of swelling in distilled water by 28% and 77% and in physiological solution by 64% and 135%, respectively. It has been proven that at room temperature all studied hydrogel samples dry in 30 hours to a moisture content within 100%. It was established that the presence of starch and carboxymethyl starch polysaccharides in the composition of the films leads to an increase in the percentage of the degree of swelling in distilled water by 55% and 107%, respectively, and to a decrease in the degree of swelling in physiological solution by 13% and 40%, respectively. It has been proven that the addition of a PVA solution of Kr and KMK solutions to the aqueous extract of the medicinal chamomile Matricaria chamomilla leads to a decrease in viscosity with an increase in the shear stress of the films. Originality. The possibility of obtaining films and hydrogels based on the aqueous extract of medicinal chamomile Matricaria chamomilla with the addition of polysaccharides has been proven. It was established that the sorption capacity of hydrogels in distilled water and physiological NaCl solution increased with the introduction of polysaccharides, and for films, the degree of swelling in distilled water increased, and in physiological NaCl solution it decreased. It has been proven that the viscosity of the studied polymer systems decreases with an increase in shear stress when the polysaccharides Kr and KMK are introduced into the composition. Practical value. The technology for the production of films and hydrogels based on the aqueous extract of medicinal chamomile Matricaria chamomilla was developed and the effect of Kr and KMK on the physical properties of polymer compositions and products based on them was investigated. Recommendations are provided on the possibility of using PVA films and hydrogels based on the aqueous extract of Matricaria chamomilla in cosmeceuticals, taking into account the sorption properties.